TENDINŢELE PROCESULUI DE GLOBALIZARE ŞI IMPACTUL SĂU ASUPRA SISTEMULUI RELAŢIILOR INTERNAŢIONALE - Conacu, Vasile (CEP USM, 2016)
In the beginning of the XXI century, human society is marked by unprecedented changes, whose effects produce a series of upgrading the major cultural , social , political and general human values paradigms. On the one hand, we live in a world characterized by dynamism, but on the other hand, by uncertainty, of course if we look realistically at our social life. The 1990 was the end of a historical cycle, with the fall of the Berlin Wall and the fall of the communist regimes in Eastern Europe.An unprecedented year of transformations followed. It modified the architecture of the international system: the dissolution of the Soviet Union, the affirmation of the USA as the main superpower on the planet, the events from the 11th of September 2001, the global economic crisis which started in 2008. The configuration of a multipolar world takes place through the extension of power and authority of some global actors, such as: states, international organizations, corporations, and the factor of cooperation between the old pillars of power and the new emerging powers represent the new challenge of the moment. In other words, we have assisted a true imbalance of power, characterized by the monopoly of global domination, which was accomplished by one single superpower: the USA. In this context, the problem of international domination has to be analyzed by taking into account political, economic, social and cultural perspectives. The increasing development of the global economy during the last two decades is the main argument in this regard, which makes us analyze which the main tendencies are and what their impact on international relation is.
Keywords: globalization; international relations; global politics; global economy; global ecologic crisis